Avaliação do desempenho de recursos energético distribuídos conectados à rede sob diferentes condições de impedância de rede - Bitencourt, Igor Antônio Baldissera de (2021)
This work aims to evaluate the performance of Distributed Energy Resources of Grid-Connected Photovoltaic Systems when inserted in different grid impedance conditions. For this purpose, first a brief literature review was conducted on the international, North American and Brazilian standards related to connection and low-frequency electromagnetic compatibility with the grid and the requirements for immunity to systemic disturbances to the grid, besides conducting a literature search on the performance of photovoltaic inverters in weak grids. Next, an in-depth study of the main standards related to the subject of this work was carried out. It was verified that the Brazilian standards have few requirements for immunity to systemic disturbances and low frequency electromagnetic compatibility. In this way, tests were performed in 8 samples of photovoltaic inverters available in the Brazilian market in 4 different network conditions, considering a null, a low, a medium and a high impedance, having as a basis of evaluation the requirements demanded by Brazilian standards. Tests were performed regarding power quality (DC component injection, harmonics and THD, power factor, voltage variation and frequency variation), safety (anti-islanding) and systemic disturbance supportability requirements (where differrent ride-through tests were proposed). The analyzed samples obtained divergent results among themselves, with samples that passed all the tests performed, others with a high percentage of failure, samples with critical power quality behavior, and even samples that failed the anti-hijacking test when inserted in networks with medium and high impedance.